2020
DOI: 10.1080/07481187.2020.1753852
|View full text |Cite
|
Sign up to set email alerts
|

Older people and death-thought accessibility: The association between death and older people in memory

Abstract: This work aimed to conceptually replicate and extend Martens, Greenberg, Schimel, and Landau's findings about older people as threatening future self. We conducted two studies using a lexical decision task to measure death-thought accessibility. Results showed that older people primes lead to stronger facilitation of death-related compared, with negative words. Such a facilitation is not observed with young people primes (Study 1). Moreover, the automatic association between the representation of older people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…According to the results of a lexical decision task to measure death-thought accessibility older people prime the lead to stronger facilitation of death-related compared, with negative words (Boudjemadi et al 2020). Dying is a regulatory process of the organism, and all examples of apoptosis demonstrate that wellordered living is only feasible through well-ordered dying (Krammer 2010).…”
Section: Old Age and Deathmentioning
confidence: 99%
“…According to the results of a lexical decision task to measure death-thought accessibility older people prime the lead to stronger facilitation of death-related compared, with negative words (Boudjemadi et al 2020). Dying is a regulatory process of the organism, and all examples of apoptosis demonstrate that wellordered living is only feasible through well-ordered dying (Krammer 2010).…”
Section: Old Age and Deathmentioning
confidence: 99%
“…For example, the proportion of older people will reach 35 per cent of the population in North America and Europe (United Nations, 2017). Some studies suggest that the constant increase in the proportion of older people is a major predictor of prejudice, stereotypes, and discriminatory behaviours toward older individuals (Boudjemadi, Posner, & Bastart, 2022; Marques et al, 2020; North & Fiske, 2015).…”
mentioning
confidence: 99%
“…Past research suggested that some older people could be considered positively and as models to emulate (Hummert, 1999). In France, studies have mainly focused on the older people as a homogeneous social category and showed them to be a depreciated and dehumanized group, mainly associated with decay and death (e.g., Boudjemadi, Demoulin, & Bastart, 2017; Boudjemadi et al, 2022). In the present research, we sought to investigate whether older people could be perceived positively and elicit respect in French society.…”
mentioning
confidence: 99%